DISEMINASI PEMBENAH ORGANIK BERBASIS BIOCHAR UNTUK TANAMAN HORTIKULTURA DI KELOMPOK TANI SUGIH HATI DESA KAWO - LOMBOK TENGAH - Selvia, Siska Ita; Sukartono, Sukartono; Bakti, Lalu Arifin Aria; Fahrudin, Fahrudin; Kusumo, Bambang Hari; Hopiana, Nida (Jurnal Abdi Insani, 2024)
Community service activities were carried out at the Sugih Hati Farmers Group which develops various seasonal horticultural crops (i.e. chili, tomato, watermelon and melon) on Vertisols land in Kawo Village, Pujut District, Central Lombok. This activity aims to popularize appropriate technology in the form of biochar-based organic fertilizers to increase soil fertility and horticultural crop productivity. The use of biochar in this agricultural land is an alternative solution to improve soil quality, namely by increasing the organic matter content of the soil, water and nutrient efficiency, and reducing soil acidity due to the use of high-analysis inorganic fertilizers. Dissemination activities have been carried out using participatory methods by involving members of the farmer groups and agricultural entrepreneurs in focused discussion activities. The results of the dissemination process reported that farmers played an active role in expressing various problems and challenges faced in farming, namely land management problems, especially fertilizer management, management of planting systems/cropping patterns and control of plant pests and diseases. Thus, they agreed to utilize biochar in the planting system. The discussion also discussed the phenomenon of climate change as one of the obstacles to horticultural crop cultivation, especially drought. Farmers are very enthusiastic in understanding the business prospects of horticultural crops, especially to meet the demand of hotels, restaurants and other tourism activities particularly in the Mandalika Special Economic Zone (MSEZ), well known as KEK Mandalika.